Idea Boga w późnych pismach Immanuela Kanta - Kupś, Tomasz (Humaniora. Czasopismo Internetowe, 2021)
Kant’s position on the problem of God is radicalized under the influence of transcendental philosophy’s evolving project. The weakening position of physico-theology and the growing importance of moral theology are possible ways of describing the shift in perspective between the pre-critical period writings and the critical period writings. The separation of the area of cognition and action excludes the possibility of formulating theodicy in a classical form. God, as only a conceived idea, and its meaning is firmly grounded in practical philosophy, in which the presentation of the law is a sufficient condition for moral behaviour. In such a model, God is only an idea, but a fully functional one. This could be noticed mostly in the Opus postumum, where in analogy to God’s practical idea, Kant deduces the transcendental ether’s existence. Ether is not just a hypothesis for Kant; it is not just a ‘temporary’ or ‘contingent’ assumption made ad hoc to explain a particular experience. Still, it is a fundamental and indelible condition, a conditio sine qua non of experience in general. The non-hypothetical matter of heat (ether) is the transcendental condition of all experience, though it does not cease to be an ‘intelligible thing’, an ‘idea’. The status of this idea is entirely ‘non-theoretical’. Kant writes about the ether similarly as he writes about the idea of God, which is only conceivable but at the same time it maintains a strong ‘non-theoretical’ status. The Kantian idea of God is strongly objectified. It is not a ‘product’ of reason, but rather something ‘perceived’ by reason, a strictly theistic idea (as Erich Adickes claims). Kant’s statements, characteristic for the Opus postumum, in which God is identified with moral law, of course give grounds to suppose that the deification of practical reason can be understood as a final stage in the long process of anthropologizing God. However, these statements also allow us to consider practical reason as a new source of what is given.